The repositioned drugs disulfiram/diethyldithiocarbamate combined to benznidazole: Searching for Chagas disease selective therapy, preventing toxicity and drug resistance - Almeida-Silva, Juliana; Menezes, Diego Silva; Fernandes, Juan Mateus Pereira; Almeida, Márcio Cerqueira; Vasco-dos-Santos, Deyvison Rhuan; Saraiva, Roberto Magalhães; Viçosa, Alessandra Lifsitch; Perez, Sandra Aurora Chavez; Andrade, Sônia Gumes; Suarez-Fontes, Ana Márcia; Vannier-Santos, Marcos André (Frontiers in Cellular and Infection Microbiology, 2022)
Chagas disease (CD) affects at least 6 million people in 21 South American countries besides several thousands in other nations all over the world. It is estimated that at least 14,000 people die every year of CD. Since vaccines are not available, chemotherapy remains of pivotal relevance. About 30% of the treated patients cannot complete the therapy because of the severe adverse reactions. Thus, the search for novel drugs is required. Here we tested the benznidazole (BZ) combination with the repositioned drug disulfiram (DSF) and its derivative diethyldithiocarbamate (DETC) upon Trypanosoma cruzi in vitro and in vivo. DETC-BZ combination was synergistic diminishing epimastigote proliferation and enhancing selective indexes up to over 10-fold. DETC was effective upon amastigotes of the partially BZ-resistant Y and the multidrug-resistant Colombiana strains. The combination reduced proliferation even using low concentrations. Scanning electron microscopy revealed membrane discontinuities and cell body volume reduction. Transmission electron microscopy revealed remarkable enlargement of endoplasmic reticulum cisternae besides, dilated mitochondria with decreased electron density and disorganized kinetoplast DNA. At advanced stages, the cytoplasm vacuolation apparently impaired compartmentation. Use of fluorescent probes indicate the increased production of reactive oxygen species associated to enhanced lipid peroxidation in parasites incubated with DETC. Colorimetric and cytometric techniques indicate the downmodulation of thiol expression. DETC inhibited superoxide dismutase activity on parasites was more pronounced than in infected mice. In order to approach the DETC effects on intracellular infection, peritoneal macrophages were infected with Colombiana trypomastigotes. DETC addition diminished parasite numbers and the DETC-BZ combination was effective, despite the low concentrations used. In the murine infection the combination significantly enhanced animal survival, decreasing parasitemia over BZ. Histopathology revealed that low doses of BZ-treated animals presented myocardial amastigote, not observed in combination-treated animals. The picrosirius collagen staining showed reduced myocardial fibrosis. ALT, AST, CK and urea plasma levels demonstrated that the combination was non-toxic. As DSF can reduce the toxicity of other drugs and resistance phenotypes, such combination may be safe and effective.